From Low Engagement to High Engagement: Explaining Turkey’s Changing Engagement in the Middle East during the JDP Period - İsmail AKDOĞAN; Furkan POLAT (Gazi Akademik Bakış)
Why did Turkey shift its Middle East policy from soft power oriented approach to the security oriented one in the early 2010s? While Turkey prioritized diplomatic, commercial and economic relations during the first decade of the 2000s, it has increasingly used military means to influence the Middle East since 2011. The primary objective of this study is to ascertain the reasons behind this widely debated question in Turkish foreign policy literature. Unlike existing explanations, the main argument of the study is that the U.S. grand strategy towards Middle East appears as the most important causal factor shaping the nature of Turkey’s engagement in its region.